2017
DOI: 10.1007/s11136-017-1714-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perceived autonomy support and basic need satisfaction on quality of life in hemodialysis patients

Abstract: Autonomy support from physicians and nurses contributes to improving HD patients' HRQOL through basic need satisfaction. This indicates that staff caring for patients with severe chronic diseases should offer considerable support for patient autonomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 50 publications
2
28
1
4
Order By: Relevance
“…The results of the present study indicated that a perceived supportive environment was associated with need satisfaction. This is in line with numerous SDT studies conducted in various domains and in the health context, Chen et al (2017) showed that haemodialysis patients experienced greater basic need satisfaction and their healthrelated quality of life improved, due to the perception of a supportive environment, direction of improvement and clear guidelines provided by their physicians and nurses. Our study also highlighted that controlled competence and relatedness need were negatively associated with competence and relatedness need satisfaction, respectively.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of the present study indicated that a perceived supportive environment was associated with need satisfaction. This is in line with numerous SDT studies conducted in various domains and in the health context, Chen et al (2017) showed that haemodialysis patients experienced greater basic need satisfaction and their healthrelated quality of life improved, due to the perception of a supportive environment, direction of improvement and clear guidelines provided by their physicians and nurses. Our study also highlighted that controlled competence and relatedness need were negatively associated with competence and relatedness need satisfaction, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…Controlled socializers pressure individuals to act, think, or feel in prescribed ways and have cold interactions with them (Deci and Ryan, 2000). Several studies have shown that a need-supportive environment is linked to various positive outcomes for patients (Ng et al, 2012), such as better dental hygiene (Halvari et al, 2017), lower scores on depressive symptoms and apathy (Souesme et al, 2016), a better quality of life for haemodialysis patients (Chen et al, 2017), a greater responsibility in the management of diabetes and glycemic control (Lee et al, 2019) and a better persistence and adherence to rehabilitation programs (Scholz et al, 2006;Chan et al, 2009). However, need satisfaction does not only depend on a supportive environment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the programme created conditions for interacting with—relating to—fellow patients, family members and knowledgeable health‐care staff. Competence and relatedness can facilitate coping and promote patient autonomy . Some participating patients reported actual or anticipated changes in their patterns of health‐care utilization, expecting that they would refrain from going to the emergency room so quickly, due to the Learning Café experience.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have compared the impact of "autonomy supportive" healthcare climates on patients' need satisfaction [52]. Autonomy supportive healthcare professionals take on a patient-centered approach and promote partnership and collaboration with their patients by active listening and seeking patient input, exploring patients' values, cognitions and emotions, providing information on disease, treatment and selfmanagement in an understandable manner, and respecting patients' preference and choice, even if this does not correspond to professional recommendation [53][54][55].…”
Section: Implications For Treatmentmentioning
confidence: 99%